2017
DOI: 10.3390/molecules22060997
|View full text |Cite
|
Sign up to set email alerts
|

Metabolomics Characterization of Two Apocynaceae Plants, Catharanthus roseus and Vinca minor, Using GC-MS and LC-MS Methods in Combination

Abstract: Catharanthus roseus (C. roseus) and Vinca minor (V. minor) are two common important medical plants belonging to the family Apocynaceae. In this study, we used non-targeted GC-MS and targeted LC-MS metabolomics to dissect the metabolic profile of two plants with comparable phenotypic and metabolic differences. A total of 58 significantly different metabolites were present in different quantities according to PCA and PLS-DA score plots of the GC-MS analysis. The 58 identified compounds comprised 16 sugars, eight… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
37
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(37 citation statements)
references
References 46 publications
0
37
0
Order By: Relevance
“…In this study, we first developed an efficient UPLC-MS method to simultaneously detect 7 major target compounds in ASH and ASS. Compared with the time-consumed HPLC method, the UPLC-MS provide faster separation, higher resolution and higher sensitivity for analysis and elucidation of drug metabolism [ 13 , 38 , 39 , 40 ]. Preciously, a method for the simultaneous determination of major bioactive components in Acanthopanax senticosus (protocatechuic acid, eleutheroside B, chlorogenic acid, caffeic acid, lithium complex and isocarotenoid) by HPLC was established in 40 min [ 1 ].…”
Section: Discussionmentioning
confidence: 99%
“…In this study, we first developed an efficient UPLC-MS method to simultaneously detect 7 major target compounds in ASH and ASS. Compared with the time-consumed HPLC method, the UPLC-MS provide faster separation, higher resolution and higher sensitivity for analysis and elucidation of drug metabolism [ 13 , 38 , 39 , 40 ]. Preciously, a method for the simultaneous determination of major bioactive components in Acanthopanax senticosus (protocatechuic acid, eleutheroside B, chlorogenic acid, caffeic acid, lithium complex and isocarotenoid) by HPLC was established in 40 min [ 1 ].…”
Section: Discussionmentioning
confidence: 99%
“…Third, the combination of the two extracts could have led to the accumulation of a higher content of alkaloids and other phenolic compounds. As such compounds are known for cytotoxic activity [36][37][38], their internalization by keratinocytes along with the NPs could thus explain the high cytotoxicity of MNPs observed also on HaCaT and not just on A375 cells. Habas et al revealed an increase in LDH concentration in a dose-dependent manner [87], and Garvey et al observed no relation between LDH release and NP concentration, concluding that the assay could have interacted with the NPs [68].…”
Section: Mtt Assaymentioning
confidence: 99%
“…Due to their importance in clinical applications, the NPs are intensively investigated, and major progress was made in recent years on green synthesis techniques of nanomaterials and on assessing their biological effects on living organisms [3,4]. alkaloids for V. minor, such as vincamine [37,38]. The antitumor activity of these two plants has been thoroughly studied before in many in vitro and in vivo experiments [39][40][41][42], moreover, three Vinca alkaloids (vincristine, vinblastine, and vinorelbine) have been approved for use in cancer therapies in the United States [43].…”
Section: Introductionmentioning
confidence: 99%
“…For example, GC-MS and LC-MS were used to reveal differential responses in the flavonoid, phenylpropanoid and terpene pathways after MeJA treatment in Centella asiatica [ 19 ]. Significantly different metabolic profiling between C. roseus and Vinca minor was characterized using GC-MS and LC-MS methods [ 20 ]. Recently, metabolomic characterization based on non-targeted GC-MS of medicinal Dendrobium plants was also reported [ 21 , 22 ].…”
Section: Introductionmentioning
confidence: 99%